A DESCRIPTIVE ANALYSIS OF CHILDREN WITH GRAVES’ DISEASE ATTENDING PAEDIATRIC ENDOCRINE CLINIC, SARAWAK GENERAL HOSPITAL - Wong, Veronica Huey-Shin; Sufian, Nurul Nabilah Mohd; Cheng, Hooi Peng (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION Graves’ Disease (GD) remains the most common cause of hyperthyroidism in children. Understanding the clinical and sociodemographic factors associated with disease progression and hormonal control may provide early insights for better disease management. This study aims to provide descriptive data of children with GD attending Paediatric Endocrine clinic, Sarawak General Hospital. METHODOLOGY A retrospective cross-sectional study was conducted. Medical records of all GD children attending Paediatric Endocrine Clinic, Sarawak General Hospital in 2024 were reviewed. Sociodemographic profile, laboratory findings, treatment and response were described. SPSS v30 was used for data analysis. RESULT A total of 11 patients were identified, with mean age at diagnosis of 8.4 ± 2.1 years. Majority of patients were female (90.9%). Majority were Chinese (36.4%), followed by Malays (27.3%), Iban (27.3%) and Bidayuh. About 54.5% had positive family history of thyroid disorders and 18.2% had Down’s syndrome. The mean thyroid stimulating hormone receptor antibodies (TRAb) level at diagnosis was 24.2 ± 11.4 IU/L and the median FT4 at diagnosis was 100 pmol/L (IQR 75–100). Carbimazole was the primary treatment of all patients with mean initial dose of 0.6 mg/kg/day and highest dose of 0.7 mg/kg/day. Propranolol was prescribed to 72.7% of patients. Normalisation of FT4 was achieved in 82% of patients with an average duration of 76 days. None of the patients achieved remission. CONCLUSION While this descriptive analysis provides insight into the clinical characteristics and management patterns of children with GD, further research with larger sample size is needed to identify predictors of remission and draw definitive conclusions regarding long-term outcomes and optimal treatment strategies.